An Outline of Feminism Jurisprudence: Phases and Approaches from Nepalese Perspectives - Bhattarai, Lokendra Hari (KMC Research Journal, 2020)
Jurisprudence is a science of law. Whereas feminism jurisprudence is a philosophy of law based on political, economic and social equality of sexes. It began in 1960s and feminists believe that law is not neutral or impartial. They blame male written history which has created in a bias way it is an off-shoot of critical legal studies. There are some of the schools of feminist jurisprudence. They are as liberal feminism, radical feminism, postmodern feminism, black feminism, lesbian feminism, queer feminism, Marxist feminism. All of the feminists have the same agenda of establishing equal opportunitiesand equal rights for women in all sectors. After the promulgation of the Constitution of the Kingdom of Nepal 1990, judicial body played vital role to eliminate gender discrimination. The Interim Constitution of Nepal 2063 was more progressive than the constitution of Nepal 1990s in the issues of women’s empowerment, reproductive freedom, equality and property entitlement. The Constitution of Nepal 2015 enlarges women’s issues and has guaranteed several rights than the previous constitutions. The judicial bodies with constitutional mechanism are playing an effective role for the protection, promotion of women's rights in Nepal.